Tissue Biomarkers in Hepatocellular Tumors: Which, When, and How - Di Tommaso, Luca; Roncalli, Massimo (Frontiers in Medicine, 2017)
Few tissue markers are currently available to pathologists in the study of hepatocellular tumors. These markers should be used carefully taking into consideration not only morphology but also, and sometimes even more important, the clinical setting where the lesion to be diagnosed had developed. Glypican-3, heat shock protein 70, and glutamine synthetase (GS) are markers currently used, as a single panel, to discriminate the nature of a <2 cm hepatocellular lesion lacking radiological features of hepatocellular carcinoma (HCC) detected in a cirrhotic patient under surveillance. Their use, which can be improved by clathrin heavy chain, is mostly requested on liver biopsy. Hepatocyte paraffin 1, arginase-1, polyclonal carcinoembryonic antigen, CD10, and bile salt export pump are tissue markers used to confirm, at histology, the diagnosis of HCC made by imaging before enrollment for phase III studies on novel anti-HCC drugs. In this setting, pathologists are usually requested a conclusive diagnosis on a liver biopsy of a poorly differentiated, necrotic, enriched in stem-phenotype, carcinoma. Liver fatty acid-binding protein, serum amyloid A, C-reactive protein, prostaglandin D2 synthetase, GS, and β-catenin can be used either on biopsy or surgical specimen to classify hepatocellular adenoma into hepatocyte nuclear factor (HNF-1α) inactivated (steatotic), inflammatory, with dysregulation of sonic hedgehog and prostaglandin pathways, β-catenin mutated, and unclassified.